A design of 210 to 235 GHz fixed tuned mixer using planar Schottky diode. Issue 1 (10th November 2020) - Pushpa, Kumari; Ghosh, Jayanta; Mondal, Priyanka
Abstract: This paper presents the design of a fixed tuned 210 to 235 GHz subharmonic mixer (SHM). The mixer is designed using GaAs based planar antiparallel Schottky diode pair AP1/G2/0P95 from Rutherford Appleton Laboratory. 3D model of the Schottky diode is discussed and simulated to consider parasitic effects of the diode. Detailed design technique of each of its subsections as well as the integrated mixer circuit is presented. Nonlinear co‐simulation of the designed mixer exhibits double sideband (DSB) conversion loss less than 9.2 dB over the frequency band 210 to 235 GHz with 4 dBm of local oscillator (LO) power while the area of the rectangular printed section is 4.224 × 0.35 mm.